El método dialéctico en la formación científica de los estudiantes de pedagogía - Ponce Vargas, José Manuel (Universidad de Costa Rica, 2018)
The present article research of addressed the subject of pedagogical training as a result of the methodological factor, from the knowledge of the properties of the dialectical method; because the age of knowledge and competition demand scientifically trained professionals; the research was carried out at the higher Public Institute of Ayaviri-Puno, with the aim of establishing the effects caused by the limited knowledge of the dialectical method in the scientific training of the students of pedagogical training. The type of research was descriptive within the quantitative approach; as a research unit, it focused on 100 % of the student population in the pedagogical area, that is to say 213 students; two instruments were used to collect the data in october of 2008: the questionnaire and the Likert scale validated by means of the consistency matrix of the problem. The ordinal measurement scale was used; we consider the Dialectical Method as an variable affect to the Scientific Formation. The results established that the knowledge of the Dialectical Method in its dimensions of: contradiction, change and practice turned out to be limited; and referring to the Scientific Formation (theoretical direction, transforming attitude and strategic decision making), showed deficiencies whose attitudes are dubious. These results abowed that the shortcomings of scientific training respond to the limited and limited knowledge referred to the dialectical days should prioritize the knowledge of the properties of the dialectical method; condition that will raise the level of scientific education in the pedagogy students.